PENGUJIAN KEWENANGAN PENUNTUTAN OLEH JAKSA DALAM PERKARA TINDAK PIDANA NARKOTIKA (Studi Putusan No. 67/Pid.Sus/2025/PN Gdt) - Rido Kuncoro (JURNAL ILMIAH EDUNOMIKA, 2023)
This study examines the exercise and testing of prosecutorial authority by the Public Prosecutor in narcotics criminal cases through an analysis of Decision No. 67/Pid.Sus/2025/PN Gdt. The research departs from the position of the prosecutor as dominus litis within the Indonesian criminal justice system, where prosecutorial authority is normatively attributed by statute but practically constrained by evidentiary standards in court. Using a normative juridical method with a case study approach, this research analyzes how prosecutorial authority is implemented through indictment construction and how such authority is judicially tested through the conformity between charges and evidentiary proof at trial. The study further identifies the factors limiting prosecutorial authority in narcotics cases, including fragmented investigative facts, the absence of key offenders, difficulties in proving subjective intent, incomplete digital evidence, time pressure, and public expectations. The analysis employs Philipus M. Hadjon’s theory of attributed authority and Lawrence M. Friedman’s legal system theory to explain the interaction between legal structure, legal substance, and legal culture. The findings demonstrate that prosecutorial authority is not absolute but operates within a framework of accountability and judicial control, emphasizing the importance of proportional discretion and evidentiary precision in narcotics prosecution within Indonesian criminal justice practice and institutional realities.